Duty or desire - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Westmoreland legacy., 2019)
"Pete Higgins is an honorary Westmoreland, a man of his word--of course he'll put duty to his orphaned niece first. Too bad the temporary nanny is tempting him with every look. Myra Hollister captivates him. But she's keeping dangerous secrets, the kind that remind Pete of all he's lost before and what he can't afford to lose again..."-- Page [4] of cover.